New data on rare shrew species (Soricidae, Mammalia) distribution and biology in Belarus - Grichik, Vasilij V.; Balash, Aliaksandr V.; Rak, Aliaksandr V.; Springer, Alexandr M. (Experimental Biology and Biotechnology, 2020)
New data on the range borders in the Republic of Belarus based on the collecting in 1990 –2018 are given for four shrew species, Taiga Shrew (Sorex isodon), Miniscule Shrew (S. minutissimus), Southern Water Shrew (Neomys anomalus) and Bicolored Shrew (Crocidura leucodon). Published data on the local distribution of these species were critically analyzed. The only known locality for the Miniscule Shrew is the Berezinsky biosphere reserve, where one extra specimen was collected in the autumn of 2018. The presence of Taiga and Southern Water Shrews was confirmed for the same locality, but several additional Belarusian localities are also reported for the latter species. Eleven individuals of the Bicolored Shrew were collected in September – October 2018 near Baranavichy, Brest Region, about 75 km northeast of the nearest known locality in this region. Data on the habitat connections of these species are given as well as on morphometrics and molt of Bicolored White-toothed Shrew. A new shrew trapping method with modified trapping cylinders baited with apple vinegar developed and tested by the authors is described.
Keywords: Soricidae; fauna; trapping methods